Pengaruh Pengawasan Internal dan Kompensasi Terhadap Kinerja Karyawan yang Dimediasi oleh Disiplin Kerja: Studi pada Karyawan BLU Rumah Sakit Bhayangkara Jayapura - Makkulasse, Muh. Arsal; Tuhumena, Ruben; Ratang, Westim (Magister Manajemen Universitas Cenderawasih, 2024)
This study aims to examine and analyze the influence of internal supervision and compensation on employee performance, to examine and analyze the influence of internal supervision and compensation on work discipline, to examine and analyze the direct and indirect influence of internal supervision and compensation on employee performance through work discipline, and to examine and analyze the influence of work discipline on employee performance. The research was conducted at Bhayangkara Hospital Jayapura with a sample size of 161. The data were tested using validity, reliability, normality, and multicollinearity tests, direct hypothesis testing, and indirect hypothesis testing. Data analysis was carried out using inferential statistics, specifically path analysis. The results show that internal supervision directly and indirectly through work discipline has a significant and positive effect on employee performance. Compensation, both directly and indirectly through work discipline, also has a significant and positive effect on employee performance. Internal supervision has a significant and positive effect on work discipline. Compensation has a significant and positive effect on work discipline. Work discipline has a significant and positive effect on employee performance.